Kepemimpinan Transformasional dan Motivasi Kerja dalam Meningkatkan Kinerja Guru: Kajian Literatur Sistematis - Dwi Indrawati; Bambang Budi Wiyono; Siti Romlah (Universitas Sarjanawiyata Tamansiswa, 2025)
This study evaluates the influence of principals’ transformational leadership and work motivation on teacher performance using a Systematic Literature Review (SLR) approach. By analyzing 33 journal articles published between 2014 and 2024, the study reveals that transformational leadership plays a significant role in enhancing teacher performance. This leadership style fosters a supportive work environment, enhances teachers' professional capacities, and strengthens their motivation. Moreover, work motivation is shown to have a direct impact on teacher performance and serves as a mediating factor between leadership and performance. The synergy between transformational leadership and work motivation forms an effective strategic approach to improving teaching quality. These findings highlight the importance of combining inspirational leadership with high levels of work motivation as a key to improving teacher performance and educational quality. Therefore, the study recommends strengthening the principal's role in motivating teachers through supportive and development-oriented leadership practices.